Naltrexone at low doses (LDN) and its relevance to cancer therapy. Issue 3 (4th March 2022) - Liu, Wai M.; Dalgleish, Angus G
ABSTRACT: Introduction: Naltrexone was designed to inhibit opioid receptors without activating them and hence used to block the stimulatory effects of morphine and heroin. It was noted that in certain patients being treated with naltrexone for an opioid addiction many reported significant secondary benefit when being weaned off naltrexone. This group of patients had chronic inflammatory and autoimmune conditions and reported improvements whilst using the lower dosages of naltrexone. There have also been recent anecdotal reports of cancer resolution following the use of low doses of naltrexone (LDN). However, the mechanism of action is unclear. Areas covered: We review three mechanisms through which LDN can influence cancer progression; namely, (a) antagonism of receptors to which LDN binds, which include toll-like receptors 7–9 that lead to IL-6 suppression b) modulation of immune function in patients; and c) direct inhibition of signaling pathways involved in cancer cell control, including the priming of pro-apoptotic pathways. Expert opinion: Considering the increase in the number of anecdotal reports of activity, there will likely be a bigger drive toward using LDN in the oncological setting. These reports support clinical trials of LDN in cancer, especially when given in combination with certain chemotherapy.